Descriptive Comparative Transcriptomic Analysis of Genotype IV SHEV ORF3-Expressing HepG2 Cells - Hanwei Jiao; Chi Meng; Fengyuan Jiao; Gengxu Zhou; Lingjie Wang; Shengping Wu; Cailiang Fan; Jixiang Li; Liting Cao; Yu Zhao; Yichen Luo (Microorganisms)
Background: Swine hepatitis E (HEV) is a zoonotic infectious disease caused by the swine hepatitis E virus (SHEV). Open reading frame 3 (ORF3) is a key virulence factor in swine HEV, playing a crucial role in the release of viral particles, the modulation of the host innate immune response, and regulation of autophagy and apoptosis, etc. However, its main function and pathogenic mechanism remain incompletely understood. Results: In our study, adenoviruses ADV4-ORF3 and ADV4-GFP were successfully constructed and mediated the overexpression of enhanced green fluorescent protein (EGFP)-ORF3 and EGFP in HepG2 cells. A total of 217 differentially expressed messenger RNAs (mRNAs) were screened by high-throughput sequencing, and 27 statistically significant differentially expressed genes were screened for further quantitative real-time reverse transcription (qRT-PCR) verification by functional enrichment (Gene Ontology [GO] and Kyoto Encyclopedia of Genes and Genomes [KEGG]). They are mainly involved in six pathways: the cellular response to unfolded protein, inflammatory response, cytokine activity, TNF signaling pathway, influenza A, and pathways in cancer. In a comparative analysis of transcriptome and mRNA expression profiles of lncRNA sequencing, the results showed that 3 mRNAs of GPX1, MDM4, and CLDN and 39 transcripts overlapped and have been identified. Conclusions: Eight differential genes, HSPA1A, HSPA1B, PLD3, RELA, GPI, SAMHD1, RPS6KA4, and PIK3CB, were successfully verified. Comparing and analyzing the results of the two sequencing methods indicated that the 3 mRNAs of GPX1, MDM4, and CLDN and 39 transcripts overlapped and have been identified in SHEV ORF3-expressing HepG2 cells, which has laid a genetic foundation for the physiological function and mechanism of SHEV ORF3.